Polyphenylene sulfide fiber insulation paper with high mixing amount of muscovite and preparation process of polyphenylene sulfide fiber insulation paper

By introducing high-dose mica and aramid fibers into polyphenylene sulfide fiber insulated paper, wet forming and hot pressing treatment processes are adopted, the problems of difficulty in connecting polyphenylene sulfide fibers and poor temperature resistance and stability are solved, and the preparation of high-performance polyphenylene sulfide fiber/mica composite insulating paper is realized, which is suitable for applications in the field of mid- and low-end insulation.

CN119571672APending Publication Date: 2025-03-07SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411882207.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

It is difficult to form chemical bonds between polyphenylene sulfide fibers and mica scales, and it is not easy to form wet, the paper-forming strength is low, and the polyphenylene sulfide fibers have poor temperature resistance and stability, and paper-forming is prone to shrink after being heated, affecting the stability of the insulating application dimensions.

Method used

The preparation process of polyphenylene sulfide fiber insulating paper with high doping amount of mica is used to evade polyphenylene sulfide fiber, aramid precipitation fiber, para-aramid pulp fiber and mica sheets through polyethylene oxide solution, and high-temperature resistant polyphenylene sulfide fiber/mica composite insulating paper is made by wet forming process. It is cold pressed, vacuum drying and hot pressing to improve the mechanical and dielectric properties of the paper.

Benefits of technology

It realizes high dielectric strength, low dielectric constant and dielectric loss of polyphenylene sulfide fiber/mice composite insulating paper, ensuring excellent dielectric properties, mechanical properties and high temperature resistance of paper-based materials, while reducing production costs, and is suitable for application needs in the mid- and low-end markets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571672A_ABST
    Figure CN119571672A_ABST
Patent Text Reader

Abstract

The invention relates to the technical crossing field of polyphenylene sulfide fiber paper, special papermaking and insulation paper, in particular to polyphenylene sulfide fiber insulation paper with high content of muscovite and a preparation process of the polyphenylene sulfide fiber insulation paper with the high content of muscovite. Polyphenylene sulfide fibers with high cost performance and high market acceptance are preferably selected as raw materials, aramid precipitation and aramid pulp are used as adhesives, and the polyphenylene sulfide fiber insulation paper with the high content of muscovite is prepared. High-temperature-resistant and high-insulation muscovite flakes are used as functional components with low dielectric loss, low dielectric constant and thermal shrinkage resistance, a wet papermaking process is adopted to prepare the polyphenylene sulfide fiber insulation paper with high muscovite doping amount, the insulation paper has excellent thermal stability and low dielectric loss characteristics, the dielectric strength is guaranteed, meanwhile, the dielectric loss value is low, and the insulation performance is good. And the production process flow is short, the production process is pollution-free, and the method can be applied to the middle-end insulation market.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the cross-field of polyphenylene sulfide fiber paper, special papermaking and insulating paper technology, and in particular to polyphenylene sulfide fiber insulating paper with a high amount of muscovite added and a preparation process thereof. Background Art

[0002] Mica flakes are a natural mineral. Their special multi-layered silicon oxide structure endows mica with high insulation, corona resistance, high temperature resistance and chemical stability, making it an indispensable auxiliary material for special cable insulation. Aramid mica paper is a thin sheet material made by combining aramid fiber as a reinforcing material with mica flakes. It combines the excellent mechanical properties of aramid fiber with the excellent electrical insulation properties of mica, and can be widely used as an insulating layer in a variety of electrical equipment such as motors and transformers. However, due to the high cost of aramid fiber and its smooth, hydrophobic and inert surface, traditional aramid mica insulation paper has weak interface bonding and high production costs, making it difficult to meet the application needs in the field of medium and low-end insulation.

[0003] As a high-performance engineering plastic, polyphenylene sulfide (PPS) has excellent high temperature resistance, chemical corrosion resistance, flame retardancy, insulation and excellent mechanical properties. It can work stably for a long time at a temperature as high as 200-220°C and can resist corrosion from a variety of acids, alkalis and organic solvents. In terms of electrical insulation, PPS has excellent electrical insulation properties, small dielectric constant, low dielectric loss, and high dielectric strength, making it an excellent electrical insulation material. In addition, the production cost of polyphenylene sulfide fiber is much lower than that of aramid fiber, and it is expected to become the most excellent insulation material in the mid- and low-end markets.

[0004] However, it is difficult to form chemical bonds between polyphenylene sulfide fibers and mica flakes, making them difficult to form by wet method. The strength of the finished paper is low, and polyphenylene sulfide fibers have poor temperature stability. The finished paper is prone to shrinkage after being heated, causing dimensional instability in insulation applications and affecting further applications. Summary of the invention

[0005] In order to solve the problem that insulating paper has unstable size due to poor temperature resistance of polyphenylene sulfide fiber and easy shrinkage when heated, the present invention provides polyphenylene sulfide fiber insulating paper with a high content of muscovite and a preparation process thereof. The present invention is achieved through the following technical solutions: A polyphenylene sulfide fiber insulation paper with a high content of muscovite and a preparation process thereof, comprising the following steps: S1, using polyethylene oxide solution as a dispersant, adding water to disintegrate polyphenylene sulfide fiber, meta-aramid fibrid, para-aramid pulp fiber, and muscovite flake to obtain mixed fiber A; S2, using a wet forming process to homogenize the mixed fiber A and vacuum filter and dehydrate it to form a wet paper web B; S3, the wet paper web B is subjected to cold pressing treatment, vacuum drying treatment and hot pressing treatment in sequence to obtain a high temperature resistant polyphenylene sulfide fiber / muscovite composite insulation paper C.

[0006] Preferably, in S1, the length of the polyphenylene sulfide fiber is 3-6 mm, the diameter is 0.75-0.89 dtex, the average fiber length of the meta-aramid fiber is 0.6-1.0 mm, the degree of fibrillation is 45-55° SR, and the specific surface area is 8-12 m 2 / g; the average fiber length of para-aramid pulp fiber is 0.9-1.3mm, the degree of fibrillation is 40-48°SR, and the specific surface area is 7.5-10m 2 / g.

[0007] Preferably, in S1, the mass ratio of polyphenylene sulfide fiber, aramid precipitated / pulp fiber, and muscovite mica sheet is (30-40) wt%: (50-60) wt%: (5-10) wt%.

[0008] Preferably, in S1, the dispersant is a polyethylene oxide solution with a concentration of 0.1 wt%-1 wt%.

[0009] Preferably, in S1, the ratio of polyphenylene sulfide fiber, aramid fiber, aramid pulp fiber, dispersant and deionized water is (0.7536-1.0048) g: (0.7536-0.0943) g: (0.5024-0.6029) g: (0.1256-0.2512) g: (10-20) mL: (0.8-1.2) L.

[0010] Preferably, in S2, the parameters of the wet forming process are: dehydration time is 5-10s, and vacuum suction pressure is 1-5MPa.

[0011] Preferably, in S3, the pressure during the cold pressing treatment is 5-10 MPa, and the pressing time is 5-8 min.

[0012] Preferably, in S3, the vacuum drying process is carried out at a temperature of 100-105° C. and a drying time of 10-15 min.

[0013] Preferably, in S3, the pressure during the hot pressing treatment is 13-15 MPa, the temperature is 180-200° C., and the time is 12-20 min.

[0014] A high temperature resistant polyphenylene sulfide fiber / muscovite composite insulating paper using a preparation process for polyphenylene sulfide fiber insulating paper with a high content of muscovite.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a process for preparing polyphenylene sulfide fiber insulation paper with a high content of muscovite. The process uses polyphenylene sulfide fiber as a skeleton, aramid fibrils and aramid pulp fibers as fillers and adhesives, mica sheets as low dielectric loss, low dielectric, and heat shrinkage resistance functional components, and polyethylene oxide as a dispersant to prepare high-temperature resistant polyphenylene sulfide fiber / muscovite composite insulation paper with high dielectric strength, low dielectric constant, and dielectric loss. The paper-based material has excellent dielectric properties, mechanical properties, and high-temperature resistance, and has the advantages of moderate raw material prices, convenient processing, and the like.

[0016] Specifically, in order to solve the problem that polyphenylene sulfide fiber has poor heat resistance and stability and is easy to shrink after being heated, the present invention introduces muscovite sheets as low dielectric loss and heat shrinkage resistant functional components of heat-resistant insulating paper. On the one hand, muscovite sheets can effectively reduce the dielectric constant and dielectric loss of composite paper and reduce current leakage by virtue of their excellent sheet structure and natural high resistivity. On the other hand, since muscovite sheets themselves are highly crystalline minerals, their crystal form will not change even at a high temperature of thousands of degrees, and they have excellent heat resistance and dimensional stability, so that muscovite sheets can play the role of "skeleton" in composite paper and effectively inhibit the thermal deformation and shrinkage of paper at high temperatures.

[0017] Meta-aramid fibrils are introduced as auxiliary fibers, fillers and adhesives. On the one hand, aramid fibrils have good water dispersion properties, which can assist the uniform dispersion of polyphenylene sulfide fibers, prepare high-quality slurry and improve the uniformity of paper. On the other hand, the aramid fibrils interface has rich amino and carboxyl groups, which can promote the close interweaving of polyphenylene sulfide fibers and mica sheets and enhance the mechanical strength of the composite paper.

[0018] Para-aramid pulp is introduced as reinforcing fiber. On the one hand, para-aramid fiber has higher modulus and strength, which helps to improve the mechanical properties of paper. On the other hand, aramid pulp has rich fiber tentacles, which helps to further promote the interweaving between fibers and mica, forming a dense structure and improving the insulation and dielectric properties of paper.

[0019] Furthermore, the present invention uses polyphenylene sulfide fiber, which is more cost-effective and has excellent temperature resistance grade on the market, as raw material, which improves the temperature resistance and chemical stability of the insulating paper and broadens the application scenarios under complex environmental conditions.

[0020] Furthermore, the drying process of the present invention has been optimized for a long time, and the preferred drying temperature is 100°C-105°C. In this temperature range, the paper fiber can be dried and dehydrated with maximum efficiency, while on the other hand, excessive energy consumption can be avoided and production safety can be achieved.

[0021] Furthermore, the present invention optimizes the high-temperature hot pressing process to soften the polyphenylene sulfide fibers and bond them to each other. The optimization of the process is based on the physical and chemical properties of aramid fibers and polyphenylene sulfide fibers, which softens the fibers to increase the bonding strength and reduce the porosity of the paper without causing the fibers to become parchment-like and age-ineffective.

[0022] Furthermore, the reagents used in the present invention are all conventional pharmaceutical reagents, which are low-toxic, cheap, and easily available, and the equipment used are all conventional instruments and equipment, which lays a foundation for the industrial production of high-temperature resistant polyphenylene sulfide fiber / muscovite composite insulating paper and improves the feasibility of the process. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a flow chart of a process for preparing polyphenylene sulfide fiber insulation paper with a high amount of muscovite added according to the present invention; Figure 2 This is a surface SEM image of the composite paper prepared in Example 1; Figure 3 This is a cross-sectional SEM image of the composite paper prepared in Example 1; Figure 4 The dielectric constant variation trend diagram of the composite paper prepared in Examples 1 to 3 at different frequencies; Figure 5 The dielectric loss variation trend diagram of the composite paper prepared in Examples 1 to 3 at different frequencies; Figure 6 The tensile strength characterization diagram of the composite paper prepared in Examples 1 to 3; Figure 7 The dielectric strength characterization diagram of the composite paper prepared in Examples 1 to 3; Figure 8 Characterization diagram of elongation at break of composite paper prepared in Examples 1 to 3; Fig. 9 The air permeability characterization diagram of the composite paper prepared in Examples 1 to 3; Fig.10 XRD characterization diagram of the composite paper prepared in Examples 1 to 3; DETAILED DESCRIPTION The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0024] The invention discloses a preparation process of polyphenylene sulfide fiber insulation paper with a high amount of muscovite, comprising the following steps: S1, placing a certain proportion of polyphenylene sulfide fiber, aramid fibrid, aramid pulp fiber, and muscovite flakes in a fiber disintegrator, adding a dispersant and deionized water, and fully disintegrating to obtain mixed fiber A; Among them, the length of polyphenylene sulfide fiber is 3-6mm, the fineness is 0.75-0.89dtex; the average fiber length of meta-aramid fiber is 0.6-1.0mm, the degree of fibrillation is 45-55°SR, and the specific surface area is 8-12m 2 / g; the average fiber length of para-aramid pulp fiber is 0.9-1.3mm, the degree of fibrillation is 40-48°SR, and the specific surface area is 7.5-10m 2 / g. The mass ratio of polyphenylene sulfide fiber, aramid precipitated / pulp fiber, and muscovite flakes is (30-40) wt%: (50-60) wt%: (5-10) wt%.

[0025] The ratio of polyphenylene sulfide fiber, aramid fiber, aramid pulp fiber, muscovite flakes, dispersant and deionized water is (0.7536-1.0048) g: (0.7536-0.0943) g: (0.5024-0.6029) g: (0.1256-0.2512) g: (10-20) mL: (0.8-1.2) L. The dispersant is a polyethylene oxide solution with a concentration of 0.1wt%-1wt%.

[0026] During dispersion, the dispersion speed is (20000~40000) revolutions, which is used to give the best dispersion process range, but is not limited to this parameter.

[0027] S2, using a wet forming process, the mixed fiber A and deionized water are mixed in a ratio of (0.8-1.2) L: (7-9) L on a standard sheeter to form a wet paper web B. The function of adding deionized water is to fully dilute and disperse the fibers. The amount of deionized water added is not limited under this parameter. The parameters of the wet forming process are: dehydration time is 5-10s, and vacuum suction pressure is 1-5MPa.

[0028] S3, the wet paper web B is subjected to cold pressing, vacuum drying and hot pressing in sequence to obtain high temperature resistant polyphenylene sulfide fiber / muscovite composite insulation paper C. During the cold pressing, the pressure is 5-10 MPa and the pressing time is 5-8 min. During the vacuum drying, the temperature is 100-105°C and the drying time is 10-15 min. During the hot pressing, the pressure is 13-15 MPa, the temperature is 180-200°C and the time is 12-20 min.

[0029] The invention discloses a polyphenylene sulfide fiber insulation paper preparation process with high muscovite content. The mica sheet is used as a low dielectric loss, low dielectric, and heat shrinkage resistant functional component to solve the problem that the insulation paper is unstable in size due to the poor temperature stability of polyphenylene sulfide fiber and easy shrinkage when heated. Aramid precipitation and aramid pulp are used as adhesives to solve the problem that polyphenylene sulfide fiber and mica sheet are not easy to be wet-formed and the strength of the finished paper is poor. At the same time, the process is low in power consumption, easy to obtain, and efficient, and has good social and economic benefits and application value.

[0030] Example 1 S1, 0.7536 g of polyphenylene sulfide fiber, 0.9043 g of aramid fibrid, 0.6029 g of aramid pulp fiber, and 0.1256 g of muscovite flakes were placed in a fiber disintegrator, 10 ml of 1 wt% polyethylene oxide solution and 0.8 L of deionized water were added, and the mixture was fully disintegrated for 20,000 revolutions to obtain mixed fiber A; S2, using a wet forming process to prepare a wet paper web B by mixing mixed fiber A and deionized water in a ratio of 0.8L:9L on a standard paper machine; S3, the wet paper web B is first cold pressed at 5 MPa for 5 min, then vacuum dried at 105°C for 10 min, and finally hot pressed at 13 MPa and 200°C for 15 min to obtain a high temperature resistant polyphenylene sulfide fiber / muscovite composite insulation paper product C.

[0031] The high temperature resistant polyphenylene sulfide fiber / muscovite composite insulation paper product C obtained in Example 1 has excellent dielectric properties, a thickness of 0.121 mm, a mechanical strength of 18.1 N / cm, a dielectric strength of 7.23 kV / mm, and a dielectric constant of only 0.01 (10 4 Hz).

[0032] Example 2 S1, 0.8792 g of polyphenylene sulfide fiber, 0.8290 g of aramid fibrid, 0.5526 g of aramid pulp fiber, and 0.2010 g of muscovite flakes were placed in a fiber disintegrator, 11 ml of 1 wt% polyethylene oxide solution and 0.9 L of deionized water were added, and the mixture was fully disintegrated for 40,000 revolutions to obtain mixed fiber A; S2, using a wet forming process to prepare a wet paper web B by mixing mixed fiber A and deionized water in a ratio of 0.9L:8.5L on a standard paper machine; S3, the wet paper web B is first cold pressed at 6 MPa for 5 min, then vacuum dried at 104°C for 10 min, and finally hot pressed at 12 MPa and 200°C for 14 min to obtain a high temperature resistant polyphenylene sulfide fiber / muscovite composite insulation paper product C.

[0033] The dielectric properties of the high temperature resistant polyphenylene sulfide fiber / muscovite composite insulation paper product C obtained in Example 2 are as follows: the thickness is 0.127 mm, the mechanical strength can reach 16.9 N / cm, the dielectric strength can reach 9.57 kV / mm, and the dielectric constant is only 0.01 (10 4 Hz).

[0034] Example 3 S1, 1.00480 g of polyphenylene sulfide fiber, 0.7536 g of aramid fibrid, 0.5024 g of aramid pulp fiber, and 0.2512 g of muscovite flakes were placed in a fiber disintegrator, 12 ml of 1 wt% polyethylene oxide solution and 1 L of deionized water were added, and the mixture was fully disintegrated for 25,000 revolutions to obtain mixed fiber A; S2, using a wet forming process to prepare a wet paper web B by mixing mixed fiber A and deionized water in a ratio of 1L:8L on a standard paper machine; S3, the wet paper web B is first cold pressed at 7 MPa for 5 min, then vacuum dried at 103°C for 10 min, and finally hot pressed at 13 MPa and 200°C for 13 min to obtain a high temperature resistant polyphenylene sulfide fiber / muscovite composite insulation paper product C.

[0035] The dielectric properties of the high temperature resistant polyphenylene sulfide fiber / muscovite composite insulation paper product C obtained in Example 3 are as follows: the thickness is 0.142 mm, the mechanical strength can reach 14.3 N / cm, the dielectric strength can reach 8.24 kV / mm, and the dielectric constant is only 0.01 (10 4 Hz).

[0036] Table 1 shows the polyphenylene sulfide / aramid composite paper prepared in Examples 1 to 3. It can be seen that the high temperature resistant polyphenylene sulfide fiber / muscovite composite insulation paper prepared by the process provided by the present invention has a thickness in the range of 0.100 mm to 0.150 mm, a dielectric strength in the range of 3.27 to 4.28, and a dielectric strength of 10 4 The dielectric constant at Hz is in the range of 0.01~0.02.

[0037] Table 1 High temperature resistant polyphenylene sulfide fiber / muscovite composite insulation paper and related technical parameters

[0038] The high temperature resistant polyphenylene sulfide fiber / muscovite composite insulation paper prepared in Examples 1 to 3 has good strength performance, high temperature stability and excellent dielectric properties. Figure 2 and Figure 3It can be seen that the aramid fibrils in the high temperature resistant polyphenylene sulfide fiber / muscovite composite insulation paper prepared by the present invention are randomly distributed and evenly and tightly interwoven with the polyphenylene sulfide fibers, which improves its mechanical strength while reducing the current path, thereby avoiding the accumulation of charges in pores and defects, reducing the local electric field strength, and achieving an overall improvement in dielectric strength. Figure 6 , 7 ,8 It can be seen that when the PPS content is 30 wt%, the tensile strength of the paper sample is 18.1 N / cm, the elongation at break is 3.98%, and the dielectric strength is 7.23 kV / mm.

[0039] Depend on Figure 4 and Figure 5 It can be seen that with the increase of frequency, the dielectric constant and dielectric loss of polyphenylene sulfide fiber / muscovite composite paper gradually decrease. When the frequency is large enough, both tend to be stable. When the polyphenylene sulfide fiber content is 30-45wt%, the composite paper is 10 4 The dielectric constant at Hz is 0.01, and the dielectric properties are excellent.

[0040] Depend on Fig. 9 It can be seen that the air permeability of the composite paper increases with the increase of PPS content. When the PPS content is 40%, the air permeability can reach 1.90 μm / (Pa·s).

[0041] Depend on Fig.10 It can be seen that the characteristic diffraction peaks of muscovite are at 8.9°, 26.8°, 36.0°, and 45.5°, corresponding to the four crystal planes (002), (006), (008), and (010), respectively. In addition, there are obvious diffraction peaks at 18.7° and 20.7°, representing the (110) and (200) crystal planes of the PPS crystal structure, respectively, indicating that the polyphenylene sulfide fibers are relatively uniformly doped in the paper structure; at the same time, it can be clearly seen that the characteristic peaks of polyphenylene sulfide cover the characteristic peaks of aramid fiber precipitation.

[0042] The present invention also discloses a high-temperature resistant polyphenylene sulfide fiber / muscovite composite insulation paper prepared by a process for preparing polyphenylene sulfide fiber insulation paper with a high amount of muscovite. Figure 3 As shown in the dense structure, the composite paper has excellent heat resistance and chemical corrosion resistance, and the production process is short and pollution-free, which can reduce its industrial production cost, improve the heat resistance and chemical stability of insulating paper for mid- and low-end applications to a certain extent, and broaden its application areas in more severe environments, with good economic benefits and application value.

[0043] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.

Claims

1. A process for preparing polyphenylene sulfide fiber insulation paper with high muscovite content, characterized in that: The following steps are involved: S1, using polyethylene oxide solution as a dispersant, adding water to dispersing polyphenylene sulfide fiber, meta-aramid precipitate, para-aramid pulp, and muscovite flakes to obtain mixed fiber A; S2, using a wet forming process to homogenize the mixed fiber A and vacuum filter and dehydrate it to form a wet paper web B; S3, the wet paper web B is subjected to cold pressing treatment, vacuum drying treatment and hot pressing treatment in sequence to obtain polyphenylene sulfide fiber insulation paper C with high content of muscovite.

2. The process for preparing polyphenylene sulfide fiber insulation paper with high muscovite content according to claim 1, characterized in that: In S1, the polyphenylene sulfide fiber length is 3-6 mm, the fineness is 0.75-0.89 dtex; the average fiber length of meta-aramid fibrils is 0.6-1.0 mm, the degree of fibrillation is 45-55° SR, and the specific surface area is 8-12 m 2 / g; the average fiber length of para-aramid pulp fiber is 0.9-1.3mm, the degree of fibrillation is 40-48°SR, and the specific surface area is 7.5-10m 2 / g.

3. The process for preparing polyphenylene sulfide fiber insulation paper with high muscovite content according to claim 1, characterized in that: In S1, the mass ratio of polyphenylene sulfide fiber, aramid fibrid, aramid pulp fiber, and muscovite flake is (30-40) wt%: (50-60) wt%: (5-10) wt%.

4. The process for preparing polyphenylene sulfide fiber insulation paper with high muscovite content according to claim 1, characterized in that: In S1, the concentration of the polyethylene oxide solution is 0.1wt%-1wt%.

5. The process for preparing polyphenylene sulfide fiber insulation paper with high muscovite content according to claim 1, characterized in that: In S1, the ratio of polyphenylene sulfide fiber, aramid fiber, aramid pulp fiber, muscovite mica flakes, dispersant, and deionized water is (0.7536-1.0048) g:(0.7536-0.0943) g:(0.5024-0.6029) g:(0.1256-0.2512) g:(10-20) mL:(0.8-1.2) L.

6. The process for preparing polyphenylene sulfide fiber insulation paper with high muscovite content according to claim 1, characterized in that: In S2, the parameters of the wet forming process are: dehydration time is 5-10s, and vacuum suction pressure is 1-5MPa.

7. The process for preparing polyphenylene sulfide fiber insulation paper with high muscovite content according to claim 1, characterized in that: In S3, during the cold pressing process, the pressure is 5-10 MPa and the pressing time is 5-8 min.

8. The process for preparing polyphenylene sulfide fiber insulation paper with high muscovite content according to claim 1, characterized in that: In S3, during the vacuum drying treatment, the temperature is 100-105°C, the vacuum degree is 0.6-0.9MPa, and the drying time is 10-15min.

9. The process for preparing polyphenylene sulfide fiber insulation paper with high muscovite content according to claim 1, characterized in that: In S3, during the hot pressing treatment, the pressure is 13-15 MPa, the temperature is 180-200° C., and the time is 15-20 min.

10. Polyphenylene sulfide fiber insulation paper produced by the preparation process of polyphenylene sulfide fiber insulation paper with high muscovite content as claimed in any one of claims 1 to 9.